2010
DOI: 10.1177/1538574410390712
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Vein Turndown Repair in Superior Mesenteric Vein Trauma: A Reasonable Alternative

Abstract: There is little information regarding the feasibility and success of this technique in traumatic SMV disruption. Future studies are required to assess its role in abdominal vascular trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…There are several cases in the literature of SMV repair using a splenic vein turndown repair [66]. Phillips [66] reported a case of splenic vein turndown repair in conjunction with distal pancreatectomy and splenectomy after blunt abdominal trauma, which resulted in good mesenteric perfusion and no congestion or edema. This repair can be used in patients with SMV injury who also sustained severe pancreatic and splenic trauma necessitating a distal pancreaticosplenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several cases in the literature of SMV repair using a splenic vein turndown repair [66]. Phillips [66] reported a case of splenic vein turndown repair in conjunction with distal pancreatectomy and splenectomy after blunt abdominal trauma, which resulted in good mesenteric perfusion and no congestion or edema. This repair can be used in patients with SMV injury who also sustained severe pancreatic and splenic trauma necessitating a distal pancreaticosplenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a splenic vein turndown technique has been successfully described in cases of SMV/PV trauma [9]. Phillips et al reported the use of the turndown technique in one patient to repair SMV traumatic avulsion, and in a literature review of 56 articles, identified five other trauma cases where the splenic vein turndown repair was used.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips et al reported the use of the turndown technique in one patient to repair SMV traumatic avulsion, and in a literature review of 56 articles, identified five other trauma cases where the splenic vein turndown repair was used. Of the six patients, four survived the procedure with radiological evidence of portal venous flow postoperatively [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although a few isolated case reports describe successful SMV revascularization through saphenous vein bypass shunts or splenic vein turndown, this is rare and occurs in high volume centers with the assistance of experienced vascular surgeons. [45][46][47]…”
Section: Superior Mesenteric Vein Injurymentioning
confidence: 99%